Functional Connectivity of the Macaque Posterior Parahippocampal Cortex - Vincent, Justin L. (American Physiological Society, 2010)
Neuroimaging experiments in humans suggest that regions in parietal cortex and along the posterior midline are functionally connected to the medial temporal lobe and are active during memory retrieval. It is unknown whether macaques have a similar network. We examined functional connectivity in isoflurane-anesthetized macaques to identify a network associated with posterior parahippocampal cortex (PPHC). Functional connectivity was observed between the PPHC and retrosplenial, posterior cingulate, superior temporal gyrus, and inferior parietal cortex. PPHC correlations were distinct from regions in parietal and temporal cortex activated by an oculomotor task. Comparison of macaque and human PPHC correlations revealed similarities that suggest the temporal-parietal region identified in the macaque may share a common lineage with human Brodmann area 39, a region thought to be involved in recollection. These results suggest that macaques and humans may have homologous PPHC-parietal pathways. By specifying the location of the putative macaque homologue in parietal cortex, we provide a target for future physiological exploration of this area's role in mnemonic or alternative processes.